2000
DOI: 10.1007/bf02490812
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Gibbs free energies of tris(β-diketonato) chromium (III),-cobalt(III), and bis(β-diketonato)palladium(II) in reversed-phase liquid chromatography on octadecyl-bonded silica gel with acetonitrile-water mobile phases

Abstract: Key WordsColumn liquid chromatography Gibbs free energy Octadecyl-bonded silica gel Liquid-liquid partition coefficient SummaryTo clarify the mechanism of retention of several fldiketonates of chromium(III), cobalt(III), and palladium(II) in reversed-phase liquid chromatography (RPLC), their capacity factors (k) were measured on an octadecyl-bonded silica gel (ODS) stationary phase with acetonitrile-water binary mobile phases. The values obtained were compared with the liquid-liquid partition coefficients (P) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The van't Hoff plots showed that platinoid metal β-diketonates operate on the same retention mechanism at 25-45 • C. Optimum conditions for the separation of four platinoid metal β-diketonates are: 40% MeOH, polymeric C 18 column and 45 • C 165 . In order to clarify the mechanism of retention of several β-diketonates of chromium(III), cobalt(III) and palladium(II), their Gibbs free energies were evaluated in RP-LC on C 18 more quantitative treatment of the Gibbs free energy of the interaction of solutes with the stationary phase, which is in accordance with the additivity of Gibbs free energy 166 . Capacity factors have been measured for several β-diketonates of Cr(III) and Pd(II) on C 18 -bonded silica stationary phases with a MeOH-H 2 O mobile phase.…”
Section: Reverse Phase Hplcmentioning
confidence: 96%
“…The van't Hoff plots showed that platinoid metal β-diketonates operate on the same retention mechanism at 25-45 • C. Optimum conditions for the separation of four platinoid metal β-diketonates are: 40% MeOH, polymeric C 18 column and 45 • C 165 . In order to clarify the mechanism of retention of several β-diketonates of chromium(III), cobalt(III) and palladium(II), their Gibbs free energies were evaluated in RP-LC on C 18 more quantitative treatment of the Gibbs free energy of the interaction of solutes with the stationary phase, which is in accordance with the additivity of Gibbs free energy 166 . Capacity factors have been measured for several β-diketonates of Cr(III) and Pd(II) on C 18 -bonded silica stationary phases with a MeOH-H 2 O mobile phase.…”
Section: Reverse Phase Hplcmentioning
confidence: 96%